Thermodynamic and electrophysical properties of a new semiconductor based on oxides of rare-earth and transition metals - Turdiyev, M.T.; Kasenov, B.K.; Nukhuly, A.; Bekturganov, Zh.S.; Kasenova, Sh.B.; Sagintaeva, Zh.I.; Kuanyshbekov, E.E. (Karagandy University of the name of academician E.A. Buketov, 2025)
The study focuses on the investigation of a new compound that combines the properties of manganites and zirconates, paving the way for the development of highly efficient functional materials. The compound was synthesized through the interaction of lanthanum oxide, zirconium oxide, manganese oxide, and sodium carbonate at temperatures ranging from 800 to 1200 °C and studied using X-ray analysis methods, including the determination of cubic lattice parameters. The analysis of the temperature dependence of heat capacity revealed second-order phase transitions, based on which equations describing its variations were derived. Thermodynamic characteristics such as entropy and enthalpy were calculated. Electrophysical measurements confirmed the semiconductor nature of the material within a specific temperature range and revealed high values of dielectric permittivity, surpassing those of reference materials
Keywords: manganite; lanthanum; zirconium; sodium; heat capacity; thermodynamic functions